Digital Discourse on the “Kabur Aja Dulu” Narrative on X: Implications for Strategic Communication, Defense, and Diplomacy - Peni Hanggarini; Rizki Damayanti (INJECT (Interdisciplinary Journal of Communication), 2026)
This study analyzes the “kaburajadulu (“Run Away First’) discourse as a form of digital public communication within Generation Z and government (officials and community leaders). Based on a multidisciplinary communication approach that integrates digital communication studies, political communication, media studies, and strategic communication, this study examines how narratives on X shape public perceptions and national discourse and generate implications for strategic communication, defense, and diplomacy.  Using a mixed research method grounded in big data analytics and media content analysis, this study analyzes 180,115 conversations from 148,710 Twitter/X users of Indonesians aged 19 to over 50 years old and reports from three leading media of Detik, Kompas, and Tribun from December 1, 2024, to March 31, 2025. Based on sentiment analysis and Latent Dirichlet Allocation (LDA), the study finds that 42.7% of netizens express direct support for “running away.” It is primarily motivated by the desire to pursue work and an education overseas. While 7% explicitly intend to renounce their citizenship because there is no future in Indonesia. The government indirectly encourages this movement by appearing neutral and introspective. The study finds that the discourse demonstrates how digital narrative and digital solidarity are rooted in declining trust toward the government. The study highlights the role of media and online platforms in constructing strategic narratives that extend beyond individual expression into broader socio-political implications. These communicative processes have important consequences for Indonesia’s non-kinetic defense and diplomacy, particularly the potential normalization of brain drain, the weakening of the national identity narrative, social division, and the impact on Indonesia’s international image and diaspora engagement. In the age of digital populism, the study suggests the significance of developing strategic communication, digital literacy, and public diplomacy narratives in order to reestablish trust and promote national resilience.